The Effect of Ease of Transaction and Service Quality on Purchasing Decisions Mediated by Consumer Satisfaction (Studies on Okeped Jabodetabek Users). - Melitina Tecoalu; Soegeng Wahyoedi; Edward Kustiawan (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
This study aims to determine the effect of ease of transaction and service quality on customer satisfaction in purchasing decision making. In this study using a sample of 100 respondents using convience sampling non profitability. Data obtained through questionnaires, the data collection process in this study is Structural Equation Modeling (SEM) with the SmartPLS (Partial Least Square) 3.0 program to determine the relationship between the effect of Ease of Transaction, Service Quality on Purchasing Decisions and Consumer Satisfaction as a mediating variable.The results of the hypothesis that there are 4 accepted and 3 rejected after being tested by hypothesis testing is done using the probability value and the t statistic. So in the hypothesis acceptance criteria t-statistic> t-table. Ease of transaction affects customer satisfaction, so the hypothesis is accepted. Service quality affects customer satisfaction, so the hypothesis is accepted. Ease of transaction affects purchasing decisions, so the hypothesis is accepted. Service quality affects purchasing decisions, so the hypothesis is accepted. Consumer satisfaction has no effect on purchasing decisions, so the hypothesis is rejected. The service quality on purchasing decisions is not mediated by consumer satisfaction well so that the hypothesis is rejected. Ease of transaction on purchasing decisions is not mediated in consumer satisfaction well, so the hypothesis is rejected. In this study, it is explained that the purchasing decision is not well mediated by consumer satisfaction so that consumers who do not reach their expectations feel dissatisfied, which leads to not making purchasing decisions on Okeped.